Considering the Role of Physical Therapists Within the Treatment and Rehabilitation of Individuals With Eating Disorders: An International Survey of Expert Clinicians. (12th August 2015) - Soundy, Andy; Stubbs, Brendon; Probst, Michel; Gyllensten, Amanda Lundvik; Skjaerven, Liv Helvik; Catalan‐Matamoros, Daniel; Vancampfort, Davy
Abstract: Purpose: Recent research has demonstrated that physical therapy may benefit the physical and mental health of people with eating disorders (EDs). Because this is a new and developing field, this study aimed to investigate the experience, practices and knowledge of international physical therapy experts to inform clinical practice, education and research. Methods: An international cross‐sectional survey design was undertaken with experienced physical therapists within the field of EDs. Physical therapist responses were analysed with descriptive statistics and thematic analysis as appropriate. Results: Twenty‐eight international physical therapists participated. On average, participants had 6.9 years (95% confidence interval: 3.1–10.7, n = 27) of clinical experience working in ED settings and devoted approximately 39.3% (95% confidence interval: 23.8–54.8, n = 27) of their time to treating individuals with EDs. Participants reported that physical therapy interventions have a diverse range of benefits on the physical, mental and disease‐specific factors (e.g. binges) in people with EDs. The key role of physical therapists includes improving body awareness, especially during physical activity combined with psycho‐education about healthy doses of physical activity. Physical therapists were able to identify a range of barriers and facilitators to physical activity in people with EDs. Discussion: This paper provides a first step towards understanding the role and value of physical therapists working with individuals with EDs. Copyright © 2015 John Wiley & Sons, Ltd.